Thermal fatigue behavior of reinforced concrete column used as heater and energy storage. Issue 7 (May 2023) - Özrahat, Evrim; Dirikgil, Tamer; Ünalan, Sebahattin
In this study, the damage effects of a new building heating system that activates the reinforced concrete columns (RC) which are the structural elements of the building by thermal cycles were investigated. The research was carried out experimentally on real-time data. The thermal fatigue effect that will occur after the structural RC is exposed to repeated thermal cycles was evaluated with the lateral cyclic loading test. The effect of the applied thermal cycles on the microstructure of the concrete was also tried to be observed. According to the data obtained in this study, in the preferred concrete type and geometry, the mechanical performance of the RC was not adversely affected at preferred operating temperatures and the number of applied thermal cycles. The results obtained are very promising in terms of the applicability of the new system as a preliminary study. In the proposed system, structural elements will be used as heater and energy storage throughout the life of the building. Therefore, it is essential to predict the exact thermal stress and strain values that the RC will be exposed to, and most importantly, the thermal fatigue life of the structural element under different parameters by future work.